A Student with Disability from Several Points of View – Roads and Off-roads of Fulfilling Educational Needs in the Mainstream School - Gajdzica, Zenon (Przegląd Badań Edukacyjnych (Educational Studies Review), 2015)
The article aims at presenting the disabled student from several possible points of view which result from overlapping categories: visible – invisible and looked-after – neglected. An attempt is made at defining the indicated categories more accurately and at situating them in the school classroom space. The author’s intention is not to describe the practice itself but rather to construct a particular concept which might be applied as a possible perspective in identifying and explaining the situation of a disabled student being part of compulsory schooling in the inclusive form.